Dynamic external force feedback loop control of a robot manipulator using a neural kompensator-Application to the trajectory following in an unknown environment - Ferguene, Farid; Toumi, Redouane (Zielona Góra: Uniwersytet Zielonogórski)
Force/position control strategies provide an effective framework to deal with tasks involving interaction with the environment. One of these strategies proposed in the literature is external force feedback loop control. It fully employs the available sensor measurements by operating the control action in a full dimensional space without using selection matrices. The performance of this control strategy is affected by uncertainties in both the robot dynamic model and environment stiffness.
Keywords: force/position control; external structure; neural control; robot manipulator